2022
DOI: 10.3390/rs14143262
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of CYGNSS Reflectivity through Wetlands’ and Deserts’ Dielectric Permittivity

Abstract: The reflection of Global Navigation Satellite Systems (GNSS) signals, namely GNSS-Reflectometry (GNSS-R), has recently proven to be able to monitor land surface properties in the microwave spectrum, at a global scale, and with very low revisiting time. Moreover, this new technique has numerous additional advantages, including low cost, low power consumption, lightweight and small payloads, and near real-time massive data availability, as compared to conventional monostatic microwave remote sensing. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…The main difference between GNOS-R and SMAP-R is their polarization properties; the latter uses HR and VR polarization, which are very different from the present GNOS-R, CYGNSS, and other GNSS-R missions. However, the future GNOS-R payloads on FY-series satellites will have the potential of full polarization [41], which will benefit the vegetation and soil moisture monitoring. With the help of the fully physical scattering models designed oriented to GNOS-R, i.e., the LAGRS model, the scattering properties of different land cover types, such as desert, highly forested, or around water, can be analyzed in detail and the corresponding retrieval methods for these land types will be presented in our following work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference between GNOS-R and SMAP-R is their polarization properties; the latter uses HR and VR polarization, which are very different from the present GNOS-R, CYGNSS, and other GNSS-R missions. However, the future GNOS-R payloads on FY-series satellites will have the potential of full polarization [41], which will benefit the vegetation and soil moisture monitoring. With the help of the fully physical scattering models designed oriented to GNOS-R, i.e., the LAGRS model, the scattering properties of different land cover types, such as desert, highly forested, or around water, can be analyzed in detail and the corresponding retrieval methods for these land types will be presented in our following work.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the incident angle, we limit our data to angles lower than 65 • , which is a range widely adopted in CYGNSS angle limitation. In terms of the signal-to-noise ratio (SNR), we pass over all the SNRs lower than −5 dB [41]. This part is often called quality control (QC).…”
Section: Lagrs-based Soil Moisture Retrievalmentioning
confidence: 99%
“…In recent decades, Global Navigation Satellite System Reflectometry (GNSS-R) has demonstrated significant potential for retrieving geophysical parameters. Although the technique was originally designed to measure sea winds in tropical oceans [5], some recent studies and projects have demonstrated the sensitivity of reflected signals from the land surface to hydrological parameters, such as SM [6][7][8], mapping flood [9,10], wetlands [11,12], and vegetation [13,14]. Retrieving SM from spaceborne GNSS-R data has become a research hotspot due to its unique advantages (such as faster revisit time, all-weather operation, and lower payload costs).…”
Section: Introductionmentioning
confidence: 99%